From political economy to economics : method, the social and the historical in the evolution of economic theory - Milonakis, Dimitris; Fine, Ben (Economics as social theory., 2009)
Shows how economics was once rich, diverse, multidimensional and pluralistic. Details how political economy became economics through the desocialisation and dehistoricisation of the dismal science.